Bacillus promotes invasiveness of exotic Flaveria bidentis by increasing its nitrogen and phosphorus uptake. (24th April 2021) - Chen, Xue; Li, Qiao; Wang, Yan; Chen, Fengxin; Zhang, Xiaoya; Zhang, Fengjuan
Abstract: The effect of exotic plants on Bacillus diversity in the rhizosphere and the role of Bacilli in exotic or native plant species remain poorly understood. Flaveria bidentis is an invasive grass in China. Setaria viridis is a native grass and occurs in areas invaded by F. bidentis . Our objectives were (i) to examine the differences in the Bacillus communities between F. bidentis and S. viridis rhizospheres soil, and (ii) to compare the effects of Bacilli from F. bidentis and S. viridis rhizospheres on the competitiveness of the invasive species. Flaveria bidentis monoculture, mixture of F. bidentis and S. viridis and S. viridis monoculture were designed in the field experiment. Bacillus diversity in their rhizosphere was analyzed using 16S rRNA. One of the dominant Bacilli in the rhizosphere soil of F. bidentis was selected to test its effect on the competitive growth of F. bidentis in a greenhouse experiment. Bacillus diversity differed in F. bidentis and S. viridis rhizosphere. Brevibacterium frigoritolerans was the dominant Bacilli in the rhizosphere of both F. bidentis and S. viridis ; however, its relative abundance in the F. bidentis rhizosphere was much higher than that in the S. viridis rhizosphere. In addition, B. frigoritolerans in the F. bidentis rhizosphere enhanced the growth of the plant compared with that of S. viridis by improving the nitrogen and phosphorus levels. This study showed that F. bidentis invasion influenced Bacillus communities, especially B. frigoritolerans, which, in turn, facilitated F. bidentis growth by increasing the levels of available nitrogen and phosphorus.